Cloud Feedback on Earth's Long‐Term Climate Simulated by a Near‐Global Cloud‐Permitting Model. Issue 15 (10th August 2022) - Yan, Mingyu; Yang, Jun; Zhang, Yixiao; Huang, Han
Abstract: The Sun becomes brighter with time, but Earth's climate is roughly temperate for life during its long‐term history; for early Earth, this is known as the faint young Sun problem (FYSP). Besides the carbonate‐silicate feedback, recent researches suggest that a long‐term cloud feedback may partially solve the FYSP. However, the general circulation models they used cannot resolve convection and clouds explicitly. This study re‐investigates the clouds using a near‐global cloud‐permitting model without cumulus convection parameterization. Our results confirm that a stabilizing shortwave cloud feedback does exist, and its magnitude is ≈6 W m −2 or 14% of the energy required to offset a 20% fainter Sun than today, or ≈10 W m −2 or 16% for a 30% fainter Sun. When insolation increases and meanwhile CO2 concentration decreases, low‐level clouds increase, acting to stabilize the climate by raising planetary albedo, and vice versa. Plain Language Summary: The emergence and evolution of life require a relatively stable climate environment. In the solar system, life has been found only on Earth and appeared since about four billion years ago. The underlying mechanisms for maintaining the long‐term climate on Earth is an important question but the answer is not completely clear. In this study, we re‐investigate a recently proposed mechanism, a stabilizing cloud feedback, using a high‐resolution cloud‐permitting model in a near‐global domain. Our simulations confirm that a stabilizing cloud feedback does exist, but its magnitude is relatively small. Key Points: A near‐global cloud‐permitting model with a resolution of 10 × 14 km is employed to test whether there is a long‐term cloud feedback The cloud feedback does have a net cooling effect when the Sun becomes brighter and meanwhile the CO2 concentration decreases These results confirm that cloud feedback is a part of the solution to the faint young Sun problem but its magnitude is relatively small